Escalation of Terrorism in the Sahel Region and Information and Communication Technology, 2018-2023: Treading an e-Counterterrorism Path - JoshuaJones Oguadinma (Revista de Direito, Estado e Telecomunicações)
[Purpose]The current innovations in information and communication technology, as demonstrated by computers and smart phones with social media platforms and applications, are believed to have enhanced and sustained terrorist campaigns currently widespread in the Sahel. In the interim, violent extremism apparently reduced in other parts of the world while the Sahel region has turned into a hub of terror attacks with an up to 43% spike in fatality rates by global ranking. The paper explored the nexus between the current upsurge of violent extremism in the Sahel region and worldwide usage of Information Technology.[Methodology/approach/design]The social-learning and frustration-aggression theories logically analyzed the phenomenon while qualitative method of data collection was adopted, including key informant interviews.[Findings]The study revealed that the ICT applications were a major contributor to the escalation of terrorism in Sahel region and deemphasized the sole reliance on internal military actions; while encouraging international collaborations among the states to embrace an aspect of artificial intelligence (AI) branded e-counterterrorism, to tackle the menace. [Practical implications]Again, addressing poverty and unemployment rates adequately can help lower the humanitarian crises triggering restiveness in the region.